Usability of Multicultural counseling self-efficacy-Racial diverse (Mcse-Rd) on the sample of Malaysian undergraduate counselor trainees - Harun, Maizatul Mardiana; Wan Jaafar, Wan Marzuki; Ismail, Asmah (Human Resource Management Academic Research Society, 2020)
Based on Self-Efficacy Theory, multicultural counseling self-efficacy is derived from the self-efficacy concept. It is usually measured together when measuring multicultural counseling competence. This study aims to examine the usability of Multicultural Counseling Self-Efficacy- Racial Diverse (MCSE-RD) on the sample of undergraduate counselor trainees in the Malaysian context. The usability is measured through investigating the adapted and Malay translated MCSE-RD psychometric properties such as its factor structure, reliability and validity. There are 205 counselor trainees from local universities who completed the questionnaire. The factor analysis resulted in the adapted MCSE-RD’s three-factor structure with 16 items were confirmed. Findings showed that MCSE-RD possessed excellent reliability as the internal consistency was ? = .966 and construct reliability of .938. For construct validity, the values of the MCSE-RD’s items were in the range of r = .681 to .870. The convergent validity value obtained the confirmatory factor analysis was .836. As the factor structure, reliability, and validity were all confirmed, the usability of the Malay translated MCSE-RD was also warranted. Moreover, its high reliability and good validity resulted that MCSE-RD can successfully be used by counselor trainees across gender and ethnicity.